The Firm-Specific Determinants of Outward Foreign Direct Investment from India - Mein, Nathalie M.L. (2009)
This study analyses the firm-specific determinants of the rapid expansion in outflows of foreign direct investment from India, and the spurt in foreign acquisitions by Indian firms during the past decade. The economic stimulus and the strategic motive for the internationalisation of firms from India were provided partly by a range of firm-specific determinants. A series of empirical models are estimated to: first, determine the factors that influence the outward investment decision; and second, determine the extent to which these factors influence the amount invested. Emphasis is also placed on the role of the pharmaceutical sector. In addition I carry out Heckman’s two-stage technique to test for the presence of selection bias.